Primary testicular diffuse large B-cell lymphoma (germinal centre B-cell type) masquerading as spermatocytic seminoma: a morphological conundrum - Verma, Amit K.; Lilha, Siddharth; Yadav, Geeta; Agarwal, Preeti; Gupta, Avneet (International Journal of Research in Medical Sciences, 2025)
Diffuse large B cell lymphoma is usually known for proliferation for medium to large abnormal lymphoid cells. Intermixed polymorphous cells may be seen in occasional cases. This type of morphology when seen in testicular lymphoma in an adult male may be misinterpreted as spermatocytic seminoma as seen in the reported case of a 48-year-old male with slow growing testicular mass. Immunohistochemistry is a must to confirm diagnosis and hence impart correct treatment in these type of cases. Spermatocytic seminoma is CD117, SALL 4 positive whereas DLBCL will display LCA, CD20, CD10, and/or bcl-6, MUM1 expression.